2021
DOI: 10.5539/elt.v14n6p25
|View full text |Cite
|
Sign up to set email alerts
|

Insights into CEFR and Its Implementation through the Lens of Preservice English Teachers in Thailand

Abstract: The Common European Framework of Reference for language teaching, learning, and assessment (CEFR) provides a guideline for English teaching aids and curriculum development in language courses. It identifies and describes the specific skills that language learners must acquire to improve their English language proficiency for communication (CoE, 2001). In the Thai context, the Ministry of Education (MoE, 2014) has adopted the framework as a practical handbook for reforming English teaching at all levels. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…One shared factor across the three levels is the understanding of the CEFR and the actionoriented approach, which appears to be the fundamental element that needs to be established before the implementation of the framework and its approach. Consistent with previous studies, it was found that practitioners in the language education system require a more thorough understanding of the CEFR and the action-oriented approach (Kanchai, 2019;Phoolaikao & Sukying, 2021). Indeed, a lack of understanding can result in an unwillingness to apply the approach into classroom practices (Franz & Teo, 2017).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…One shared factor across the three levels is the understanding of the CEFR and the actionoriented approach, which appears to be the fundamental element that needs to be established before the implementation of the framework and its approach. Consistent with previous studies, it was found that practitioners in the language education system require a more thorough understanding of the CEFR and the action-oriented approach (Kanchai, 2019;Phoolaikao & Sukying, 2021). Indeed, a lack of understanding can result in an unwillingness to apply the approach into classroom practices (Franz & Teo, 2017).…”
Section: Discussionsupporting
confidence: 65%
“…The CEFR framework has been adopted in numerous countries across the world, including Thailand. However, more in-depth studies are required to provide a clearer picture of the implementation of the CEFR framework and, more importantly, its underlying action-oriented approach in classrooms (Kanchai, 2019;Phoolaikao & Sukying, 2021). The current findings have revealed three substantial implications.…”
Section: Implications and Conclusionmentioning
confidence: 79%
See 1 more Smart Citation
“…Due to the CEFR's widespread implementation in educational systems, its strengths on global policymaking are now more apparent. The discussion of the adaptation of CEFR in mny contexts is in line with [15] who claimed that the CEFR played a pivotal role in English language teaching and learning and was a useful tool for curriculum guidelines, English language courses, assessments, and describing language proficiency levels. Besides that, a recent study by [16] revealed participants' understanding that the CEFR is an essential and beneficial guideline for English language teaching classrooms.…”
Section: Resultsmentioning
confidence: 59%
“…Studies have shown that language educators displayed various attitudes, reactions, and perceptions towards CEFR. Among popular issues that arose due to its implementation in many countries that have adopted it reported in studies were insufficient training on the CEFR familiarization to guide teachers adequately to take CEFR into their classroom practices, and limited knowledge and exposure to the CEFR among teachers (Ajop & Said, 2020;Alih et al, 2020;Díez-Bedmar & Byram, 2019;Foley, 2019;Kaur & Mah, 2018;Kok & Aziz, 2019;Phoolaikao & Sukying, 2021;Tosun & Glover, 2020;Uri & Aziz, 2018). In regards with the insufficient training, thus, it is a fundamental need to be addressed that most English as Second Language (ESL) teachers expressed their concerns and they claimed that they need more inservice training on CEFR (Sülü & Kır, 2014;Singh et al, 2021), and a series of training and workshop on CEFR (Khair & Shah, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%